Engine Gearbox Fault Diagnosis Using Modified Elman Neural Network and ACO Algorithm - Song, Chong Zhi; Wu, Hai Chao (Applied Mechanics and Materials, 2012)
Analyzed the shortcomings of Elman network, the paper put forward a modified Elman network, combined Ant Colony Optimization (ACO) algorithm to train the modified Elman network, and implement trained NN (Neural Network) to fault diagnosis of engine gearbox. Using conventional ’frequency domain’ analysis method, modified Elman network fault diagnosis of the gearbox was carried out. The results proved that fault diagnosis of engine gearbox based on the modified Elman neural network and ACO has better precision and diagnoses gearbox effectively, which imp roves the effectiveness and quality of the diagnosis.